2020
DOI: 10.3390/ijms21030807
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Inflammation is a Marker for Risk of Post-Infarct Ventricular Dysfunction and Heart Failure

Abstract: Acute ST-segment elevation myocardial infarction (STEMI) activates inflammation that can contribute to left ventricular systolic dysfunction (LVSD) and heart failure (HF). The objective of this study was to examine whether high-sensitivity C-reactive protein (CRP) concentration is predictive of long-term post-infarct LVSD and HF. In 204 patients with a first STEMI, CRP was measured at hospital admission, 24 h (CRP24), discharge (CRPDC), and 1 month after discharge (CRP1M). LVSD at 6 months after discharge (LVS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
42
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(47 citation statements)
references
References 58 publications
2
42
1
Order By: Relevance
“…In addition, low-grade inflammation and oxidative stress contribute to the pathophysiology of obesity, atherosclerosis, T2DM, and MetS [ 5 , 63 , 64 , 65 , 66 ]. Elevated C-reactive protein (CRP) levels, which are related to insulin resistance and MetS, are independent predictors of CVD events [ 63 , 67 , 68 , 69 , 70 , 71 ]. Oxidative stress is associated with adiposity, impaired insulin signaling pathways, insulin resistance, and increased risk of cardiometabolic diseases [ 64 , 72 , 73 , 74 ].…”
Section: Impact Of Circadian Rhythms and Circadian Rhythm Disruptimentioning
confidence: 99%
“…In addition, low-grade inflammation and oxidative stress contribute to the pathophysiology of obesity, atherosclerosis, T2DM, and MetS [ 5 , 63 , 64 , 65 , 66 ]. Elevated C-reactive protein (CRP) levels, which are related to insulin resistance and MetS, are independent predictors of CVD events [ 63 , 67 , 68 , 69 , 70 , 71 ]. Oxidative stress is associated with adiposity, impaired insulin signaling pathways, insulin resistance, and increased risk of cardiometabolic diseases [ 64 , 72 , 73 , 74 ].…”
Section: Impact Of Circadian Rhythms and Circadian Rhythm Disruptimentioning
confidence: 99%
“…Chronic pathological disorders, including cardiovascular diseases (CVDs) [ 1 , 2 ], neurodegenerative diseases [ 3 , 4 ], diabetes [ 5 , 6 ], metabolic syndrome [ 7 , 8 ], and cancer [ 9 , 10 ] share an inflammatory microenvironment as a hallmark [ 11 ]. A Common feature of these complex diseases is the activation of “sterile” inflammatory pathways, in which immune cells represent relevant effectors and drivers for the onset and progression of the disease [ 12 ], due to their extreme capability to reshape their phenotype [ 13 ], to functionally [ 14 ], metabolically [ 15 , 16 ] adapting to the surrounding environment.…”
Section: Introductionmentioning
confidence: 99%
“…The pathophysiology of post-infarct LVSD is complex and poor understood [5]. Much evidence has revealed that processes such as myocardial injury associated with infarct size, left ventricular remodelling, myocardial stress, oxidative stress, and local and systemic inflammatory responses are all involved in the pathophysiology of post-infarct LVSD [5,[7][8][9]. Recent studies further indicated that stress-induced hyperglycaemia (SIH) and concomitant metabolic perturbations also play an extremely important role in the initiation and progression of post-infarct LVSD [10][11][12].…”
mentioning
confidence: 99%